Blade runner (1982) [videorecording (DVD)] : [the final cut] - Scott, Ridley; Ford, Harrison, 1942-; Hauer, Rutger, 1944-2019-; Young, Sean; Olmos, Edward James; Dick, Philip K. (Distributed by Warner Home Video, 2010)
Los Angeles, 2019: Rick Deckard of the LAPD's Blade Runner unit prowls the steel & microchip jungle of the 21st century. His job is to track down and eliminate assumed humanoids known as 'replicants.' Replicants were declared illegal after a bloody mutiny on an Off-World Colony, and are to be terminated upon detection. He wants to get out of the force, but is drawn back in when 6 "skin jobs," the slang for replicants, hijack a ship back to Earth. The city that Deckard must search for his prey is a huge, sprawling, bleak vision of the future.